The Effect of Return on Assets and Debt to Equity Ratio on Earnings Per Share - Amalya, Neneng Tita; Sulistyani, Tri; Harsono, Yhonanda; Fakhresi, Aditya Rizky (IJESS International Journal of Education and Social Science, 2025)
The purpose of this study is 1) to determine the effect of Return on Assets (ROA) on Earning Per Share (EPS) at PT Darya-Varia Laboratoria Tbk for the period 2013-2022. 2) to determine the effect of Debt to Equity Ratio (DER) on Earning Per Share (EPS) at PT Darya-Varia Laboratoria Tbk for the period 2013-2022. 3) To determine the direction of Return on Assets (ROA) and Debt to Equity Ratio (DER) on Earning Per Share (EPS) simultaneously at PT Darya-Varia Laboratoria Tbk for the period 2013-2022. The research method used in this study is quantitative research with a descriptive and associative approach. The data analysis technique uses Descriptive Statistical Test, Classical Assumption Test, Multiple Linear Regression Test, Hypothesis Test and Determination Coefficient Test. The results of this study are 1) Return On Asset (ROA) partially has a significant effect on Earning Per Share (EPS) at PT Darya-Varia Laboratoria Tbk for the period 2013-2022. This is evidenced by the Return On Assets (ROA) variable obtained a t-value of 5.332 with a significance value of 0.001. 2) Debt to Equity Ratio (DER) partially has a significant effect on Earning Per Share (EPS) at PT Darya-Varia Laboratoria Tbk for the period 2013-2022. This is evidenced by the Debt to Equity Ratio (DER) variable obtained a t-value of 3.396 with a significance value of 0.012. 3) Return On Assets (ROA) and Debt to Equity Ratio (DER) simultaneously have a significant effect on Earning Per Share (EPS) at PT Darya-Varia Laboratoria Tbk for the period 2013-2022. This is proven by the results of the simultaneous test with an F-table of 4.74, obtaining an F-count value of 18.013 and a significance value of 0.002.